Mammals show faster recovery from capture and tagging in human-disturbed landscapes - Stiegler, Jonas; Gallagher, Cara A.; Hering, Robert; Müller, Thomas; Tucker, Marlee; Apollonio, Marco; Arnold, Janosch; Barker, Nancy A.; Barthel, Leon; Bassano, Bruno; Beest, Floris M. van; Belant, Jerrold L.; et al. (Nature communications, 2024)
Wildlife tagging provides critical insights into animal movement ecology, physiology, and behavior amid global ecosystem changes. However, the stress induced by capture, handling, and tagging can impact post-release locomotion and activity and, consequently, the interpretation of study results. Here, we analyze post-tagging effects on 1585 individuals of 42 terrestrial mammal species using collar-collected GPS and accelerometer data. Species-specific displacements and overall dynamic body acceleration, as a proxy for activity, were assessed over 20 days post-release to quantify disturbance intensity, recovery duration, and speed. Differences were evaluated, considering species-specific traits and the human footprint of the study region. Over 70% of the analyzed species exhibited significant behavioral changes following collaring events. Herbivores traveled farther with variable activity reactions, while omnivores and carnivores were initially less active and mobile. Recovery duration proved brief, with alterations diminishing within 4–7 tracking days for most species. Herbivores, particularly males, showed quicker displacement recovery (4 days) but slower activity recovery (7 days). Individuals in high human footprint areas displayed faster recovery, indicating adaptation to human disturbance. Our findings emphasize the necessity of extending tracking periods beyond 1 week and particular caution in remote study areas or herbivore-focused research, specifically in smaller mammals. In wildlife tagging, stress from capture and handling can alter post- release behavior and potentially study interpretations. This study of 42 mammal species shows that these effects diminish within 4–7 days, and quicker for animals in high human activity areas indicating adaptation to disturbance.